Lived Experiences of People Living with Type II Diabetes: A qualitative study - Sharma, Sarswati; Joshi, Sarala (Journal of Advanced Academic Research, 2017)
Introduction: Nepal is experiencing a double disease burden: Communicable diseases as well as rising incidence of non-communicable diseases. It is believed to be due to unhealthy life style and faulty food habit. Among the NCD Diabetes Mellitus (DM) is considered to be a major health problem. Methods: This study has adapted Phenomenological approach in which the researcher has tried to explore the perceptions and beliefs of people living with type 2 diabetes. In this study two instruments were used; in-depth interview were taken in 21 respondents who are attending different hospitals of Kathmandu. The interview was guided by using open ended questions. All interviews were analyzed manually and qualitative content analysis was done to identify the codes, categorizes, sub categorizes concepts data and to find out the main theme. Results: Most of the respondents believed that unhealthy diet(high carbohydrate, high fat, low rough phage food), sedentary life style, stressful life and consumption of the food with higher concentration of pesticides (eg: Metacid). Conclusions: People perceived that unhealthy life style is the main cause of diabetes and to reduce the number awareness program should be initiated by the government mainly in the public places and should be kept in the school level curriculum also.